Місце та значення міжнародних нормативно-правових актів у системі джерел трудового права України - Могілевський, Л. В.; Mohilevskyi, L. V.; ORCID: http://orcid.org/0000-0002-6994-6086 (Юридична наука. - 2020. - № 5 (107), т. 2. - С. 203-209, 2020)
Запропоновано авторське визначення поняття міжнародного нормативно-правового акту. Аргументовано, що за критерієм юридичної сили міжнародні нормативно-правові акти посідають майже найвище місце в ієрархії нормативно-правових актів, що входять до системи трудового права. Відзначено важливість застосування норм міжнародного законодавства у національній правові системі. Наголошено, що міжнародно-правові акти посідають особливе місце серед інших структурних елементів системи джерел трудового права, так як встановлюють світові загальні стандарти й основи реалізації особами права на працю, визначають загальні механізми й основи правового регулювання трудових і тісно пов’язаних із ними правовідносин.

The relevance of the article is that an important component of the implementation of the principle of the rule of law in labor law is the recognition by the state of the priority of international legal acts over national law. In addition, the ongoing integration processes into the European community in our country, in particular the desire for a visa-free regime with many European countries, the introduction of an open market space, obliges Ukraine to participate in numerous international events, to establish ties with many international communities and organizations, to recognize international standards, including in the field of labor policy. The article, based on the analysis of scientific views of scientists and the norms of current legislation, proposes the author’s definition of the concept of international legal act. It is argued that by the criterion of legal force, international regulations occupy almost the highest place in the hierarchy of regulations that are part of the labor law system. The importance of application of the norms of the international legislation in the national legal system is noted. It is concluded that international legal acts occupy a special place among other structural elements of the system of sources of labor law, as they establish global common standards and bases of realization of the right to work, determine general mechanisms and bases of legal regulation of labor and closely related legal relations. . According to such a criterion as legal force, international legal acts occupy almost the highest place in the hierarchy of normative legal acts that are part of the labor law system. An international legal act as a structural element of the system of sources of labor law is an official act concluded in accordance with legally established procedures between Ukraine and another party (parties) of international law, the form of which is established by international standards and rules. provisions of which are the legal regulation of labor and closely related legal relations.

Предложено авторское определение понятия международного нормативно правового акта. Аргументировано, что по критерию юридической силы международные нормативно правовые акты занимают почти самое высокое место в иерархии нормативно правовых актов, входящих в систему трудового права. Отмечена важность применения норм международного законодательства в национальной правовой системе. Отмечено, что международно-правовые акты занимают особое место среди других структурных элементов системы источников трудового права, так как устанавливают мировые общие стандарты и основы реализации лицами права на труд, определяют общие механизмы и основы правового регулирования трудовых и тесно связанных с ними правоотношений.
The place and significance of international regulations in the system of sources of labor law of Ukraine
Могілевський, Л. В. Місце та значення міжнародних нормативно-правових актів у системі джерел трудового права України / Могілевський Л. В. // Юридична наука. - 2020. - № 5 (107), т. 2. - С. 203-209. - DOI: https://doi.org/10.32844/2222-5374-2020-107-5-2.25.
Могілевський, Л. В. (2020). МІСЦЕ ТА ЗНАЧЕННЯ МІЖНАРОДНИХ НОРМАТИВНО-ПРАВОВИХ АКТІВ У СИСТЕМІ ДЖЕРЕЛ ТРУДОВОГО ПРАВА УКРАЇНИ. Юридична наука, 2(5(107), 203–209. https://doi.org/10.32844/2222-5374-2020-107-5-2.25.
Keywords: Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; правовий акт; legal act; правовой акт; міжнародно-правовий акт; international legal act; международно-правовой акт; джерела трудового права; sources of labor law; источники трудового права; трудові правовідносини; labor legal relations; трудовые правоотношения